Perioperative outcomes of multiport or single-port, transperitoneal or retroperitoneal robot assisted radical nephroureterectomy: a narrative review - Gabriel, Pierre-Etienne; Shariat, Shahrokh F.; Rouprêt, Morgan; Sfakianos, John P.; Xylinas, Evanguelos (Frontiers in Oncology, 2025)
BackgroundRobot-assisted radical nephroureterectomy (RARNU), performed via either a multiport or single-port approach through transperitoneal or retroperitoneal routes, is an increasingly utilized surgical method for patients with upper tract urothelial carcinoma.Materials and methodsA collaborative review of the literature available on Medline was conducted to report the perioperative outcomes of multiport or single-port, transperitoneal or retroperitoneal RARNU. A total of 31 references published between 2006 and 2023 were included.ResultsThe multiport transperitoneal robotic approach has been documented in 23 studies including between 10 and 3774 RARNU. Operative times ranged from 157 to 326 minutes, intraoperative complication rates from 0% to 7.3%, estimated blood loss from 68.9 mL to 380 mL and blood transfusion rates from 1.4% to 22.7%. Overall postoperative complication ranged from 11.9% to 43.8%, with major complications occurring in 0% to 15.1% of cases. Additionally, the length of hospital stay ranged from 2.3 to 10.3 days. The single-port transperitoneal robotic approach has been documented in 3 studies including between 1 and 12 RANU. Operative time ranged from 160 to 240 minutes, with 17% of patients requiring transfusions. The length of stay varied between 3 and 7 days. Finally, five retrospective studies, including between 2 and 12 patients treated with multiport retroperitoneal RARNU and between 2 and 20 patients with single-port retroperitoneal RARNU were reported, also with satisfactory results.ConclusionAlthough prospective comparative studies are needed to confirm these results, RARNU approach, whether single-port or multi-port, transperitoneal or retroperitoneal, appears promising and safe.